VD_FINDINFO HC / 2022 / 143 vom 12. Januar 2022 - VD Tribunal cantonal (2022)
COMPÉTENCE EXCLUSIVE, COMPÉTENCE RATIONE MATERIAE, CAS CLAIR, DROIT DU TRAVAIL | 2 al. 1 let. a LJT, 3 LJT, 131 al. 2 LP, 257 CPC (CH)